1990
DOI: 10.1088/0031-9120/25/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pressure: didactical transpositions and pupils' conceptions

Abstract: Using the concept of pressure two research trends-content analysis and pupils' conceptions of subject matter-are drawn together, in an attempt to understand the issues in teaching and learning specific domains of physics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
0
7
0
6
Order By: Relevance
“…In order to corroborate the findings, the data were triangulated. For instance, we asked students (13)(14) year-olds) before and after instruction, to compare the values of pressure at the same depth in two vessels containing water, for several different situations, e.g., at two different points of the water, at the backs of two divers, in small vessels, in a well, and in the sea, etc. In addition to the descriptive results, we articulated a number of mental models that are possibly used by the students in this domain, named "packed crowd model", "pressing force model" and "liquidness model", as has extensively been presented elsewhere [11].…”
Section: Students' Domain-specific Conceptions and Reasoning In The Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to corroborate the findings, the data were triangulated. For instance, we asked students (13)(14) year-olds) before and after instruction, to compare the values of pressure at the same depth in two vessels containing water, for several different situations, e.g., at two different points of the water, at the backs of two divers, in small vessels, in a well, and in the sea, etc. In addition to the descriptive results, we articulated a number of mental models that are possibly used by the students in this domain, named "packed crowd model", "pressing force model" and "liquidness model", as has extensively been presented elsewhere [11].…”
Section: Students' Domain-specific Conceptions and Reasoning In The Fmentioning
confidence: 99%
“…In the context of constructivism, clarification of the gap between students' prior knowledge and the representations of scientific knowledge is of great importance, for elaborating teaching, adapted to students' ideas and reasoning [13]. Taking such a theoretical perspective, we carried out a content analysis of six well-known textbooks on introductory physics, looking at how the concept of pressure is introduced and treated (for more details: [13]). The six textbooks refer to general physics in different countries at three levels, i.e., junior and senior high school and tertiary education.…”
Section: Scientific Content: Representations and Transformationmentioning
confidence: 99%
“…This approach reflects a commitment to emphasize the central concept of "balance of forces," to limit the number of new concepts and terms introduced, and to try to build on students' prior conceptions. In addition, we were influenced by previous studies on pressure that found that when students interpret phenomena involving liquids, they typically ascribe to pressure the meaning of force (Kariotogloy et al, 1990).…”
Section: The Mars Curriculum 49mentioning
confidence: 99%
“…En revanche, des difficultés apparaissent pareillement pour les liquides et pour les gaz : la pression dans un fluide est généralement confondue avec les forces pressantes exercées par ce liquide (Kariotoglou et al 1990), elle est souvent associée au volume de fluide entourant un solide immergé et pas uniquement à la profondeur (ou à l'altitude) d'immersion (Kariotoglou et al 1990, Besson & viennot 2004, son action est couramment perçue verticalement et vers le bas (Engel Clough & Driver 1985, Kariotoglou et al 1990, Besson & viennot 2004) et l'isotropie n'est que très rarement envisagée. En outre, les travaux de Rozier ont montré que les étudiants associent préférentiellement pression et densité de gaz : la pression va, pour ces étudiants, avec l'idée géométrique de tassement, en excluant l'aspect microscopique cinétique (Rozier & viennot 1991).…”
Section: La Pression Dans Les Fluides : Difficultés Des éTudiants 22unclassified